(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article is devoted to the analysis of the experience of organizing technical and technological training in the maritime educational institutions of Ukraine during a pandemic. 233 Analysis of international organizations reports made it possible to characterize the impact of the COVID-19 pandemic on maritime education: on the academic schedule at maritime universities, on delivery methods of maritime education, on the availability of cadet berths and onboard training programs. The author emphasizes that in the first months of the pandemic, the administrations of maritime universities were forced to quickly look for ways to address issues of expanding the technical capabilities of platforms for online learning (the possibility of uninterrupted learning of several hundred, or even thousands of students; providing tools on the platform for all types of educational activity; collect of reports on work on the platform of students and the teaching staff) and the organization of the work of the teaching staff in the new conditions. Analysis of e-courses that provide technical and technological training showed that the transition to a new learning format allowed many teachers to introduce new approaches, modern tools and methods of forming a knowledge and skills system of future seafarers. When developing these courses, some requirements were taken into account to ensure the quality of educational materials and the effectiveness of teaching in the format of e-courses: availability of a short description of the course; the consistency and clarity of the structure of the e-course, regardless of the selected structuring format; the compliance of the course structure and content with the working curriculum of the discipline; ensuring the development of high-quality educational content; introduction of interactive learning elements using various online resources; providing feedback through any communication channels; development of effective control and evaluation procedures. In the conclusion, the author identifies several ways to further improve the quality of technical and technological training of maritime transport specialists: revision of approaches to the choice of learning formats; cooperation with the IT sector for the development of simulators and virtual laboratories that fully comply with the training programs for maritime transport specialists and the requirements of the STCW; cooperation with shipping companies on providing conditions for the implementation of online learning for cadets on board; cooperation with MOOC platforms for the development and implementation of courses from the best specialists in maritime education into the educational process.